Students' Ability in Translation Techniques (English-Gorontalo): Subtitle of Orion and The Dark Film - Dama, Idrus; Idrus, Asri (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
This study analyzes students' ability to apply translation techniques from English to Gorontalo based on the subtitles of the film "Orion and The Dark." A descriptive qualitative approach was employed, utilizing the translation techniques theory developed by Molina and Albir. A total of 261 data points were analyzed to identify the use of various translation techniques by students, including adaptation, transposition, reduction, and modulation. The results revealed that out of the 18 translation techniques proposed by Molina and Albir, students only used 7 techniques. The findings highlight students’ limitations in understanding the cultural context of both the source and target languages, which contributed to translation errors. Furthermore, the study indicates that students' ability to apply certain translation techniques is influenced by their limited contextual understanding of the texts. The study also identifies semantic and pragmatic shifts in the translation process, which may affect text coherence and reader comprehension. This research contributes to the understanding of the application of translation techniques at the local level and recommends further development in the application of amplification techniques within target language translation.